Integrating Social Work Into Interprofessional Education - Keith Adamson; Rachelle Ashcroft; Sylvia Langlois; Dean Lising (Advances in Social Work, 2020)
The University of Toronto Interprofessional Education Curriculum (IPE) is an exemplar of advancing interprofessional education with a focus on preparing students for practice in healthcare settings. Our paper begins with a detailed overview of the University of Toronto’s IPE program including the range of participating faculties, an overview of the curriculum including examples of learning activities, and the social work specific expectations that are embedded in the core and elective components. Following, is a discussion on mitigating the challenges and engaging opportunities associated with integrating social work in a healthcare-focused IPE program at a major Canadian University. Our exploration of mitigating challenges and engaging opportunities will span five key areas: a) Creating meaningful learning experiences for social work students; b) Implementing mandatory or elective IPE participation; c) Scheduling of IPE activities; d) The role of social work faculty in driving student involvement in IPE; and e) Strengthening social work professional leadership for IPE.